2018
DOI: 10.1039/c8ra07430e
|View full text |Cite
|
Sign up to set email alerts
|

Toughening of POSS–MPS composites with low dielectric constant prepared with structure controllable micro/mesoporous nanoparticles

Abstract: A promising method to improve the performance of CE composites via combining advantages of POSS and MPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For example, many studies have reported on the incorporation of caged polyhedral oligomeric silsesquioxane (POSS) hollow nanoparticles into polymers to prepare low-k nanohybrid materials. [13][14][15][16][17][18][19] However, the obvious limitations such as small size, high-cost and difficulty to synthesize prevent further applications for functionalized POSS monomers. To overcome this limitation, several research groups used inorganic nano-mesoporous silica materials such as MCM-41 and hollow silica spheres as fillers to greatly reduce the k value of silica-based nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…For example, many studies have reported on the incorporation of caged polyhedral oligomeric silsesquioxane (POSS) hollow nanoparticles into polymers to prepare low-k nanohybrid materials. [13][14][15][16][17][18][19] However, the obvious limitations such as small size, high-cost and difficulty to synthesize prevent further applications for functionalized POSS monomers. To overcome this limitation, several research groups used inorganic nano-mesoporous silica materials such as MCM-41 and hollow silica spheres as fillers to greatly reduce the k value of silica-based nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the latter improvement is often achieved at the expense of thermal stability. This deficiency is remedied by the synthesis of nanocomposites of CER with montmorillonite (MMT) [ 35 , 36 , 37 , 38 , 39 , 40 ], carbon nanotubes [ 41 , 42 ], nanostructured aluminum borate [ 43 ], ZnO [ 44 ], ZrW 2 O 8 [ 45 ], nanosilica [ 46 , 47 , 48 ], polyhedral oligomeric silsesquioxane (POSS) [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ], and other nanofillers. The most pronounced effect on mechanical and thermal properties of CERs is achieved when nanoparticles with organically modified surface are used, as they may react with polymer networks.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of reactive R, 3-D POSS molecules with diameters of 1–2 nm, they may graft chemically to polymer structures. New hybrid organic–inorganic CER-based thermosets with hydroxyl- [ 49 , 51 , 52 , 55 , 69 , 72 ], amino- [ 50 , 53 ], epoxy- [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 68 , 69 , 70 ], cyanate- [ 67 ], benzoxazinyl- [ 71 ] or methacrylate-functionalized [ 73 ] POSS units have thus been obtained with improved thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of reactive R, 3-D POSS molecules with diameters of 1-2 nm, they may graft chemically to polymer structures. New hybrid organic-inorganic CER-based thermosets with hydroxyl- [49,51,52,55,69,72], amino- [50,53], epoxy- [59][60][61][62][63][64][65][66][68][69][70], cyanate- [67], benzoxazinyl- [71] or methacrylate-functionalized [73] POSS units have thus been obtained with improved thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%